(3Ndb GdEfSGfs
(3ChdgG (B:s
(3ef GdeLdS GdKGfi hGdNeSjf s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3eLdOGfs
(3Hg VHWs
(3jTJed Ydi eGFI eLdS ai JaSjQ bhdg JYGdi ai CfaSce CadG JHUQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B447 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs